DINAMIKA GENDER DAN PERAN PEREMPUAN DALAM EKONOMI KELUARGA - Mujahidah, Mujahidah (AL-MAIYYAH, 2015)
This paper describes the dynamics and discourse of gender issues that have successfully penetrated hard paternalistic culture. Gender discourse takes attention a lot of various parties, and even have become mainstreaming which significantly influence social changes. Gender issues have broken every corner of thought and life by putting